PROSES PRODUKSI PEMBUATAN BUSHING MENGGUNAKAN MESIN BUBUT KONVENSIONAL DI PT. AMANAH JAYA PERSADA - Rachmat, Asep; Ramadhan, Saiful (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
Bushing is a mechanical component that functions to reduce friction, absorb vibration, and extend the lifespan of machine parts. This study was conducted through practical work at PT. Amanah Jaya Persada to analyze the production process of bushing using a conventional lathe machine. The research method involved observation, literature study, direct practice, and data collection. The production stages included design using Computer Aided Design (CAD), machining with a conventional lathe, finishing, and quality control. Calculations of machining parameters such as cutting speed, feed rate, depth of cut, and machining time were also performed. The results showed that the conventional lathe machine can produce bushings that meet dimensional standards and tolerances of ±0.05 mm. The success of the process depends on proper tool selection, accurate calculation, and operator skills. Although CNC machines provide higher precision, conventional lathes remain effective and economical for small to medium-scale production.